SCRUM Methodology Adoption in Designing Digital MSME Empowerment Application - Fransiska Sisilia Mukti; Fadhli Almu’iini Ahda; Sunu Jatmika (Department of Informatics Engineering, 2022)
COVID-19 pandemic has significantly reduced most of MSME revenue, including Pelangi Nusantara Singhasari Foundation (PELANUSA). Market demand has decreased drastically, many activities and production have been delayed, which have an impact on the decline in sales turnover. This forces all activities to shift to the digital realm to ensure business continuity. In fact, the process of migrating community activities from conventional systems to digitalization poses a new problem for the management. The use of platforms that are still fragmented, the lack of knowledge of digital marketing concepts, to the limitations of the management in carrying out empowerment activities, especially for members of the disabled community. Seeing this phenomenon, Institut Asia Malang collaborated with PT. Ina Gata Persada proposed an innovative solution in the form of a digital empowerment application called PELAWONS (PELANUSA for Women and Disabilities). To achieve the suitability of the purpose of PELAWONS with functionality and timeliness, it takes an analysis and proper software design. SCRUM is considered to be able to produce good quality software according to user desires, can be used in large and small projects, and easy to adopt changes. We developed PELAWONS refers to the five main steps on SCRUM process: establishing SCRUM team, defining list of the product backlogs, arranging the sprint phase, analyzing the progress through daily scrum, and evaluating the result with sprint review. SCRUM methodology adoption in designing PELAWONS proven to be able to accelerate the application development process and reduce the risk of project failure through system flexibility.